FAKTOR KEBERHASILAN BELAJAR SANTRI MADRASAH DINIYAH TAKMILIYAH (MDTA) MASJID SYUKUR RAWANG TIMUR PADANG SELATAN - Sri Astuti; Suprizen; Seprian Ilham (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study is to describe the characteristics of successful learning among MDTA students at the Syukur Mosque in South Padang, the role of teachers in supporting successful learning among MDTA students at the Syukur Mosque in South Padang, and the leadership role of the principal in supporting successful learning among MDTA students at the Syukur Mosque in South Padang. This research is a qualitative descriptive study using document review techniques, in-depth interviews, and observation. The sample in this study was a persuasive sample based on the relevance and depth of the information. This research was conducted at the Syukur Mosque Madrasah (MDTA) in South Padang in August 2024. The results of the research concluded that: first, student learning success begins with success in solving student learning problems. The characteristics of student learning success are seen from three aspects: cognitive, affective, and psychomotor. Learning success can also be seen from student achievements in both academic and non-academic fields. Second, as teachers, teachers must master the material being taught, possess good teaching methods, models, and techniques, and be able to conduct assessments. As mentors, teachers guide students to success in their learning and act as liaisons who can foster collaboration with parents. Third, the leadership of the madrasah principal as a manager, by optimizing the "golden triangle" consisting of the Ministry of Religious Affairs, parents, teachers, and the madrasah principal. Optimizing collaboration with the Ministry of Religious Affairs, because the MDTA of the Syukur Mosque in South Padang is under its auspices, supervises the teaching and learning process, from learning materials to the teaching and learning process. The madrasah principal directs, motivates, establishes harmonious relationships, and collaborates with other parties to find new innovations.